Transaction costs influence on the stability of financial market: agent-based simulation - Šperka, Roman; Spišák, Marek (Journal of Business Economics and Management, 2013)
We implement an agent-based simulation of financial market model. Agent-based simulations are used nowadays as an alternative to the traditional models, based on predetermined equilibrium state theory. Agent technology brings some kind of local intelligence and rational expectations to the decision support system of financial market participants. Agents follow technical and fundamental trading rules to determine their speculative investment positions. We consider direct interactions between speculators and they may decide to change their trading behaviour. If a technical trader meets a fundamental trader and they realize that fundamental trading has been more profitable than technical trading in recent past, the probability that the technical trader switches to the fundamental trading rules is relatively high. In particular the influence of transaction costs is studied in this paper. Transaction costs can be increased by the off-market regulation (for example in the form of taxes) on financial market stability, by overall volume of trade and other market characteristics. The paper shows a positive impact of suitable transaction costs on the financial market stability in the long run.